ІНФОРМАЦІЙНІ ТЕХНОЛОГІЇ ЯК ЗАСІБ ФОРМУВАННЯ ПРОФЕСІЙНОЇ КОМПЕТЕНТНОСТІ МАЙБУТНЬОГО ВЧИТЕЛЯ ІНОЗЕМНИХ МОВ (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2010)
The article deals with the ways of the formation of professional competition of foreign language teachers by means of the informational technologies, the experience of using the multimedia course «Reward InterN@tive» in the teaching process for students of foreign languages specialty is shown.